A composite microstructure broach imitating crab claw hair and preparation method thereof
By implanting different functional fibers on the surface of the broach teeth and combining with the composite microstructure design, the broach has solved the problems of large friction and wear, easy to collapse, blade sticking to chips, and difficult to lubricate and cool during the cutting process, and the multi-functional surface of self-cleaning, lubrication, cooling and vibration suppression is achieved, and the surface quality of the workpiece is improved.
Patent Information
- Application Number
- CN202211340991.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-30
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-10-30
AI Technical Summary
During the cutting process, existing broaches have problems such as large friction and wear, easy to collapse, blade sticking, and difficulty in lubrication and cooling, which makes it difficult to improve the surface quality of the workpiece.
The composite microstructure design of imitation crab velvet is adopted, and different functional fibers are implanted on the surface of the knife teeth through electrostatic flocking and precision dispensing technology, combined with surface microstructure laser etching and single-point diamond tool vibration imprinting technology, forming a multifunctional wetting, lubrication, cooling and vibration suppression surface.
It realizes the self-cleaning, lubrication, cooling and vibration suppression functions of the broach surface, extends the tool service life and improves the surface quality of the workpiece.
Smart Images

Figure CN115647467B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional surfaces of cutting tools, and in particular relates to a composite microstructured broach imitating crab claw hairs and a preparation method thereof. Background Art
[0002] Due to its high processing accuracy and processing efficiency, broaching is widely used in the processing and preparation of high-precision parts in the fields of aerospace, automobiles and ships. However, at present, there are problems such as large friction and wear of broach teeth, easy chipping, blade adhesion, and difficulty in lubrication and cooling in the broaching process, making it difficult to further improve the surface quality of the workpiece. Therefore, for broaching, developing a new type of broach that can enhance the cleaning, lubrication, cooling, and vibration suppression of the tooth surface is of great significance to the development of the broaching tool industry.
[0003] However, there are currently no broaches and preparation methods with outstanding surface cleaning, lubrication, cooling, and vibration suppression effects. For example, the patent with patent application number 201710533151.7 discloses an AlNbC / AlNbCN laminated coating tool and its preparation process. The patent adopts a composite coating method of unbalanced magnetron sputtering + arc ion plating. The cutting tool can be widely used in the cutting of titanium alloys, stainless steel and other materials. For example, the patent with patent application number 201610812045.8 discloses a micro-textured ZrVSiN adaptive coating tool and its preparation process. The patent uses surface coating technology to coat the surface of the cutting tool with a ZrVSiN adaptive coating. The ZrVSiN adaptive coating can generate an oxide lubricating film and store the lubricating film through micro-texture. For example, the patent with patent application number 201910393087.6 discloses a micro-textured gradient coating tool and its preparation method. The patent uses laser induced plasma technology to process micro-textures, and then uses multi-arc ion plating + medium-frequency magnetron sputtering co-deposition to prepare a coating on the tool surface. The above patents are basically research on tool lubrication and wear prevention, and do not involve research on the tool surface cleaning, cooling and vibration suppression functions. Summary of the invention
[0004] The present invention aims to solve the problems of existing broach teeth in the cutting process, such as large friction and wear, easy chipping, blade sticking, and difficult lubrication and cooling, and proposes a composite microstructure broach imitating crab claw hair and a preparation method thereof. The present invention is a multi-channel composite microstructure distribution design method imitating the multifunctional characteristics of crab claw hair, such as cleaning, lubrication and vibration suppression; a precise point flocking design method that innovatively integrates electrostatic flocking and precision dispensing technology; a preparation method that combines surface microstructure laser etching, single-point diamond tool (SPDT) vibration embossing technology with precise dispensing; a method for implanting fibers with different functional characteristics in different areas of broach teeth by electrostatic flocking technology; a surface composite microstructure broach and a preparation method thereof that integrates complex microstructure design, laser etching, single-point diamond tool vibration embossing, precision dispensing technology, precise flocking, and surface functional characteristics (wetting, lubrication, cooling, cleaning, etc.).
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] The invention discloses a composite microstructure broach imitating the hair of crab claws. The front cutting surface of each cutting tooth is provided with cylindrical pit-shaped microstructures arranged in X1 rows and Y1 columns in a rectangular shape, and two groups of opposite sides of the rectangle are respectively parallel to the rear cutting surface and the side surface of the cutting tooth; the rear cutting surface of each cutting tooth is provided with cylindrical pit-shaped microstructures arranged in X2 rows and Y2 columns in a rectangular shape, and two groups of opposite sides of the rectangle are respectively parallel to the front cutting surface and the side surface of the cutting tooth; the side surfaces of the cutting teeth on both sides of each cutting tooth are provided with cylindrical pit-shaped microstructures arranged in X3 rows and Y3 columns in a parallelogram shape, and two groups of opposite sides of the parallelogram are respectively parallel to the front cutting surface and the rear cutting surface of the tool. The diameter D of the cylindrical pit-shaped microstructure is in the range of 0.2 to 0.3 mm, and the depth H is in the range of 0.2 to 0.3 mm; carbon fibers are implanted in the cylindrical pit-shaped microstructures in odd rows on the front and rear blades of the teeth, and nylon fibers are implanted in the cylindrical pit-shaped microstructures in even rows; lead and copper mixed fibers are implanted in the cylindrical pit-shaped microstructures on the side surfaces of the teeth. The diameter d of the carbon fibers, nylon fibers, and lead and copper mixed fibers are all in the range of 5 to 10 μm, and the length L of the carbon fibers, nylon fibers, and lead and copper mixed fibers are all in the range of 0.35 to 0.4 mm; the density of the carbon fibers, nylon fibers, or lead and copper mixed fibers in the cylindrical pit-shaped microstructures is not less than 2.5*10 4 Pieces / mm 2 .
[0007] Preferably, the center distance L1 of two adjacent cylindrical pit-shaped microstructures in the same row on the front cutting face, the rear cutting face and the side surface of the tooth is within the range of 0.3 to 0.35 mm, and the center distance L2 of two adjacent cylindrical pit-shaped microstructures in the same column is within the range of 0.3 to 0.35 mm.
[0008] More preferably, the distance l from the center of the two rows of cylindrical pit-shaped microstructures on the front cutting surface closest to the side surfaces of the two teeth to the adjacent side surfaces of the teeth is min1 The distance from the center of the row of cylindrical pit-shaped microstructures closest to the blade to the back surface is l min2 The distance l from the center of the two rows of cylindrical pit-shaped microstructures on the side of the blade closest to the two sides to the adjacent side of the blade min3 The distance from the center of the row of cylindrical pit-shaped microstructures closest to the blade to the front blade surface is l min4 The distance l from the center of a row of cylindrical pit-shaped microstructures closest to the front cutting edge on the side of the tooth to the front cutting edge min5 The distance from the center of the row of cylindrical pit-shaped microstructures closest to the back face to the back face is l min6 Both are 0.2mm.
[0009] Preferably, X1=4, Y1=30; X2=7, Y2=30; X3=10, Y3=8.
[0010] Preferably, the lead and copper mixed fibers include 40% lead fibers and 60% copper fibers.
[0011] The present invention provides a method for preparing a composite microstructure broach imitating crab claw hair, which is specifically as follows:
[0012] S1. Preheat the broach to be processed at 300°C for 30 minutes and air-cool it to room temperature.
[0013] S2. Fix the broach processed in step S1 on the workbench of a laser marking machine, and input the parameters of the cylindrical pit-shaped microstructure into the laser marking machine; process X2 rows and Y2 columns of cylindrical pit-shaped microstructures with a rectangular distribution on the back face of each tooth of the broach, and process X3 rows and Y3 columns of cylindrical pit-shaped microstructures with a parallelogram distribution on the side face of each tooth.
[0014] S3, placing the broach processed in step S2 into an ultrasonic cleaning machine for ultrasonic cleaning to remove debris, the cleaning time is greater than 1 minute, and drying is performed after cleaning.
[0015] S4. Fix the broach processed in step S3 on the processing table of the tool tip microstructure single-point diamond tool vibration stamping device, input the parameters of the cylindrical pit-shaped microstructure into the tool tip microstructure single-point diamond tool vibration stamping device, and use the tool tip microstructure single-point diamond tool vibration stamping device to prepare a rectangularly distributed X1 row and Y1 column cylindrical pit-shaped microstructure on the front cutting edge of each tooth of the broach.
[0016] S5, placing the broach processed in step S4 into an ultrasonic cleaning machine for ultrasonic cleaning to remove debris, the cleaning time is greater than 1 minute, and drying is performed after cleaning.
[0017] S6. Carbon fibers are implanted in the cylindrical pit-shaped microstructures in the odd-numbered rows on the front and rear blade surfaces, nylon fibers are implanted in the cylindrical pit-shaped microstructures in the even-numbered rows, and lead and copper mixed fibers are implanted in the cylindrical pit-shaped microstructures on the side surfaces of the blade teeth.
[0018] The process for implanting carbon fiber, nylon fiber, and lead and copper mixed fiber is as follows:
[0019] Step 1: Place the broach on the processing table of the precision dispensing machine, spray adhesive on the odd-numbered rows of cylindrical pit-shaped microstructures on the front and rear cutting edges of each tooth, and let it stand for 4 minutes.
[0020] Step 2: Place the broach processed in step 1 into an electrostatic flocking machine, and implant carbon fibers into the cylindrical pit-shaped microstructures in odd rows on the front and rear blade faces of the blade teeth.
[0021] Step three, use a high-speed microscope camera to photograph the odd-numbered rows of cylindrical pit-shaped microstructures on the front and rear blades of each tooth, and transmit the photographed images to a computer for analysis to determine whether the density of the carbon fiber in the cylindrical pit-shaped microstructures in the odd-numbered rows on the front and rear blades of each tooth reaches a preset value. If the density of the carbon fiber in the cylindrical pit-shaped microstructures does not reach the preset value, remove the carbon fiber in the corresponding cylindrical pit-shaped microstructures, put the broach back into the electrostatic flocking machine, and re-implant the carbon fiber in these cylindrical pit-shaped microstructures where the carbon fiber density does not reach the preset value.
[0022] Step 4: Dry the broach after the treatment in step 3 to solidify the adhesive in the odd-numbered rows of cylindrical pit-shaped microstructures on the front and rear blade surfaces of each tooth.
[0023] Step 5: Blow air on the broach processed in step 4 to remove the carbon fibers scattered outside the cylindrical pit-shaped microstructures on the broach where the carbon fibers have been implanted.
[0024] Step 6: Place the broach on the processing table of the precision dispensing machine, spray adhesive on the even-numbered rows of cylindrical pit-shaped microstructures on the front and rear cutting edges of each tooth, and let it stand for 4 minutes.
[0025] Step 7: Place the broach processed in step 6 into an electrostatic flocking machine, and implant nylon fibers into the cylindrical pit-shaped microstructures in even rows on the rake face and the flank face of each blade tooth.
[0026] Step 8. Use a high-speed microscope camera to photograph the cylindrical pit-shaped microstructures in each even-numbered row on the front and rear blade faces of each tooth, and transmit the photographed images to a computer for analysis to determine whether the density of the nylon fiber in the cylindrical pit-shaped microstructures in each even-numbered row on the front and rear blade faces of the tooth reaches a preset value. If the density of the nylon fiber in the cylindrical pit-shaped microstructure does not reach the preset value, remove the nylon fiber in the corresponding cylindrical pit-shaped microstructure, put the broach back into the electrostatic flocking machine, and re-implant nylon fibers in these cylindrical pit-shaped microstructures where the nylon fiber density does not reach the preset value.
[0027] Step nine: drying the broach processed in step eight to solidify the adhesive in the cylindrical pit-shaped microstructures in even rows on the front and rear blade surfaces of each tooth.
[0028] Step 10: Blow air on the broach processed in step 9 to remove the nylon fibers scattered outside the cylindrical pit-shaped microstructures on which the nylon fibers have been implanted.
[0029] Step 11: Place the broach on the processing table of the precision dispensing machine, spray adhesive on each cylindrical pit-shaped microstructure on the two tooth sides of each tooth, and let it stand for 4 minutes.
[0030] Step 12: Place the broach processed in step 11 into an electrostatic flocking machine, and implant lead and copper mixed fibers into each cylindrical pit-shaped microstructure on the two tooth sides of each tooth.
[0031] Step 13, use a high-speed microscope camera to photograph each cylindrical pit-shaped microstructure on the two tooth sides of each tooth, and transmit the photographed image to a computer for analysis to determine whether the density of the lead and copper mixed fiber in the cylindrical pit-shaped microstructure on the two tooth sides of each tooth reaches a preset value. If the density of the lead and copper mixed fiber in the cylindrical pit-shaped microstructure does not reach the preset value, remove the lead and copper mixed fiber in the corresponding cylindrical pit-shaped microstructure, put the broach back into the electrostatic flocking machine, and re-implant the lead and copper mixed fiber in these cylindrical pit-shaped microstructures where the density of the lead and copper mixed fiber does not reach the preset value.
[0032] Step 14: drying the broach after the processing in step 13 to solidify the adhesive in each cylindrical pit-shaped microstructure on the two tooth sides of each tooth.
[0033] Preferably, the adhesive is thermally conductive silicone grease.
[0034] More preferably, the dosage of the adhesive used in the single cylindrical pit-shaped microstructure is 0.001 ml.
[0035] The beneficial effects of the present invention are as follows:
[0036] 1. The present invention studies the functions and distribution of crab claw hairs such as cleaning, vibration suppression and water storage, and obtains a microstructure distribution form that imitates crab claw hairs on this basis. Microstructures are provided on the front blade surface, the rear blade surface and the two side surfaces of each tooth of the broach, and the different functions of the crab claw hairs are imitated. The layered and staggered distribution of the serrated hairs and the hedgehog-like hairs on the claws of the crab have the functions of cleaning, clearing and guiding. Carbon fibers or nylon fibers are implanted in the microstructures at different positions of the front blade surface and the rear blade surface of each tooth of the broach by electrostatic flocking technology. The carbon fibers and nylon fibers are staggered, so that the surface of the broach has the functions of wetting, lubrication and liquid self-transportation, so that the broach of the present invention can self-clean chips in a lubricating liquid environment; imitating the claw-like hairs on the claws of the crab have the effects of vibration perception and vibration suppression, lead and copper mixed fibers are implanted in the microstructures of the two side blade surfaces of each tooth of the broach, so that the broach has the functions of vibration suppression and cooling.
[0037] 2. The present invention uses precision dispensing technology to make the adhesive precisely attached to the microstructure, so that the fiber can be more accurately implanted in the microstructure. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a three-dimensional diagram of the overall structure of the keyway broach of the present invention;
[0039] Figure 2 for Figure 1 A partial enlarged view of part B1;
[0040] Figure 3 This is a distribution diagram of the cylindrical pit-shaped microstructure on the blade teeth of the present invention;
[0041] Figure 4 Schematic diagram of the distribution of cylindrical pit-shaped microstructures on the front cutting edge of the present invention;
[0042] Figure 5 Schematic diagram of the distribution of cylindrical pit-shaped microstructures on the back face of the present invention;
[0043] Figure 6 Schematic diagram of the distribution of cylindrical pit-shaped microstructures on the side of the blade teeth in the present invention;
[0044] Figure 7 It is a schematic diagram of the structure of a single cylindrical pit in the present invention;
[0045] Figure 8 The present invention is a flow chart of the preparation of the broach;
[0046] Fig. 9 Schematic diagram of processing of cylindrical pit-shaped microstructure on the back face of the present invention;
[0047] Fig.10 Schematic diagram of processing of cylindrical pit-shaped microstructures on the side of the cutter teeth in the present invention;
[0048] Fig.11 Schematic diagram of processing of cylindrical pit-shaped microstructure on the front cutting edge of the present invention;
[0049] Fig.12 A schematic diagram of precise dispensing of a cylindrical pit-shaped microstructure in the present invention;
[0050] Fig.13 Schematic diagram of electrostatic flocking of cylindrical pit-shaped microstructures in the present invention;
[0051] Fig.14 Schematic diagram of the distribution of carbon fiber and nylon fiber on the front blade face and the back blade face in the present invention;
[0052] Fig.15 This is a schematic diagram of the distribution of lead and copper mixed fibers on the side of the blade teeth in the present invention;
[0053] Fig.16 The present invention is a flow chart of implanting carbon fiber, nylon fiber and lead and copper mixed fiber. DETAILED DESCRIPTION
[0054] The present invention is further described below in conjunction with the accompanying drawings.
[0055] like Figure 1 As shown, a composite microstructure broach imitating crab claw hair is used in this embodiment. A keyway broach is used, and the material is YG8 cemented carbide. The specific dimensions of the keyway broach are: total length L is 600mm, tooth width b1 is 16mm, horizontal width b2 of the back blade A3 is 2mm, the front angle γ0 of the blade is 12°, the back angle α0 is 6°, the pitch p is 6mm, and the number of teeth is 50. Figure 2 As shown, the blade teeth of the keyway broach include a rake face A1, a cutting edge A2, a flank face A3 and two blade side faces A4.
[0056] like Figure 3 , Figure 4 , Figure 5 and Figure 6 As shown, the front cutting edge A1 is provided with X1 rows and Y1 columns of cylindrical pit-shaped microstructures arranged in a rectangular shape, and the two opposite sides of the rectangle are parallel to the back cutting edge A3 and the side surface A4 of the cutter teeth respectively; the back cutting edge A3 is provided with X2 rows and Y2 columns of cylindrical pit-shaped microstructures arranged in a rectangular shape, and the two opposite sides of the rectangle are parallel to the front cutting edge A1 and the side surface A4 of the cutter teeth respectively; the side surfaces A4 of the cutter teeth on both sides are provided with X3 rows and Y3 columns of cylindrical pit-shaped microstructures arranged in a parallelogram shape, and the two opposite sides of the parallelogram are parallel to the front cutting edge A1 and the back cutting edge A3 of the cutter respectively. Figure 7As shown, the diameter D of the cylindrical pit-shaped microstructure is within the range of 0.2 to 0.3 mm, and the depth H is within the range of 0.2 to 0.3 mm; carbon fibers are implanted in the cylindrical pit-shaped microstructures in the odd-numbered rows on the front cutting surface A1 and the back cutting surface A3 of the cutter teeth, and nylon fibers are implanted in the cylindrical pit-shaped microstructures in the even-numbered rows; the staggered distribution of carbon fibers and nylon fibers enables the tool surface to have the functions of wetting, lubrication, and liquid self-transportation, so that the broach of the present invention can have the function of self-cleaning chips in a lubricating liquid environment; lead and copper mixed fibers are implanted in each cylindrical pit-shaped microstructure on the two tooth side surfaces A4 of the cutter teeth, so that the tool has the multifunctional effects of vibration suppression and cooling (the lead and copper mixed fibers are on the side surfaces of the cutter teeth, do not participate in cutting, and will not affect the processing quality, and at the same time, its functions can be maintained all the time). The diameter d of carbon fiber, nylon fiber and lead and copper mixed fiber is in the range of 5 to 10 μm, and the length L of carbon fiber, nylon fiber and lead and copper mixed fiber is in the range of 0.35 to 0.4 mm; the density of carbon fiber, nylon fiber or lead and copper mixed fiber in the cylindrical pit-shaped microstructure is not less than 2.5*10 4 Pieces / mm 2 .
[0057] As a preferred embodiment, the center distance L1 of two adjacent cylindrical pit-shaped microstructures in the same row on the front cutting surface A1, the back cutting surface A3 and the tooth side surface A4 is in the range of 0.3 to 0.35 mm, and the center distance L2 of two adjacent cylindrical pit-shaped microstructures in the same column is in the range of 0.3 to 0.35 mm.
[0058] More preferably, if Figure 4 As shown, on the front cutting edge A1, the distance l between the center of the two rows of cylindrical pit-shaped microstructures closest to the side surfaces A4 of the cutting teeth on both sides and the adjacent side surfaces A4 of the cutting teeth is min1 The distance from the center of the row of cylindrical pit-shaped microstructures closest to the blade A2 to the back face A3 is l min2 Both are 0.5mm. Figure 5 As shown, on the back face A3, the distance l between the center of the two rows of cylindrical pit-shaped microstructures closest to the tooth side faces A4 on both sides and the adjacent tooth side faces A4 is min3 The distance from the center of the row of cylindrical pit-shaped microstructures closest to the blade A2 to the front blade surface A1 is l min4 Both are 0.5mm. Figure 6 As shown in the figure, on the side surface A4 of the blade, the distance l from the center of a row of cylindrical pit-shaped microstructures closest to the front cutting surface A1 to the front cutting surface A1 is min5 The distance from the center of the row of cylindrical pit-shaped microstructures closest to the back face A3 to the back face A3 is l min6 Both are 0.2mm.
[0059] As a preferred embodiment, X1=4, Y1=30; X2=7, Y2=30; X3=10, Y3=8.
[0060] like Figure 8 As shown, the present invention provides a method for preparing a composite microstructure broach imitating crab claw hair, which is specifically as follows:
[0061] S1. Preheat the broach to be processed at 300°C for 30 minutes and air-cool it to room temperature to prevent cracks from occurring during subsequent microstructure processing.
[0062] S2, such as Fig. 9 and Fig.10 As shown, the broach processed in step S1 is fixed on the workbench of the laser marking machine, and the parameters of the cylindrical pit-shaped microstructure are input into the laser marking machine; X2 rows and Y2 columns of cylindrical pit-shaped microstructures with rectangular distribution are processed on the back cutting surface A3 of each tooth of the broach, and X3 rows and Y3 columns of cylindrical pit-shaped microstructures with parallelogram distribution are processed on the tooth side surface A4 of each tooth.
[0063] S3, placing the broach processed in step S2 into an ultrasonic cleaning machine for ultrasonic cleaning to remove debris, the cleaning time is greater than 1 minute, and drying is performed after cleaning.
[0064] S4, such as Fig.11 As shown, the broach processed in step S3 is fixed on the processing table of the tool tip microstructure single point diamond tool (SPDT) vibration stamping device, the parameters of the cylindrical pit-shaped microstructure are input into the tool tip microstructure single point diamond tool vibration stamping device, and the tool tip microstructure single point diamond tool vibration stamping device is used to prepare X1 rows and Y1 columns of cylindrical pit-shaped microstructures distributed in a rectangular shape on the front cutting edge A1 of each tooth of the broach.
[0065] S5, placing the broach processed in step S4 into an ultrasonic cleaning machine for ultrasonic cleaning to remove debris, the cleaning time is greater than 1 minute, and drying is performed after cleaning.
[0066] S6. Carbon fibers are implanted in the cylindrical pit-shaped microstructures in the odd-numbered rows on the front and rear blade surfaces, nylon fibers are implanted in the cylindrical pit-shaped microstructures in the even-numbered rows, and lead and copper mixed fibers are implanted in the cylindrical pit-shaped microstructures on the side surfaces of the blade teeth.
[0067] like Fig.16 As shown in the figure, the process of implanting carbon fiber, nylon fiber and lead and copper mixed fiber is as follows:
[0068] Step 1: Fig.12As shown, the broach is placed on the processing table of a precision glue dispensing machine, and adhesive is sprayed on the odd-numbered rows of cylindrical pit-shaped microstructures on the front cutting surface A1 and the back cutting surface A3 of each tooth, and the broach is left to stand for 4 minutes.
[0069] Step 2: Fig.13 As shown, the broach processed in step 1 is placed in an electrostatic flocking machine, and carbon fibers are implanted in the cylindrical pit-shaped microstructures in odd rows on the front cutting surface A1 and the back cutting surface A3 of the cutting teeth.
[0070] Step 3: Use a high-speed microscope to photograph the cylindrical pit-shaped microstructures of the odd-numbered rows on the front cutting surface A1 and the back cutting surface A3 of each tooth, and transmit the photographed images to a computer for analysis to determine whether the density of the carbon fiber in the cylindrical pit-shaped microstructures of the odd-numbered rows on the front cutting surface A1 and the back cutting surface A3 of each tooth reaches a preset value (e.g., 2.5*10 4 Pieces / mm 2 ), if the density of the carbon fiber in any cylindrical pit-shaped microstructure does not reach the preset value, the carbon fiber in the corresponding cylindrical pit-shaped microstructure is removed, the broach is put back into the electrostatic flocking machine, and the carbon fiber is re-implanted into these cylindrical pit-shaped microstructures where the carbon fiber density does not reach the preset value.
[0071] Step 4: Dry the broach after the treatment in step 3 to solidify the adhesive in the odd-numbered rows of cylindrical pit-shaped microstructures on the front cutting surface A1 and the back cutting surface A3 of each tooth.
[0072] Step 5: Blow air on the broach processed in step 4 to remove the carbon fibers scattered outside the cylindrical pit-shaped microstructures on the broach where the carbon fibers have been implanted.
[0073] Step 6: Fig.12 As shown, the broach is placed on the processing table of a precision dispensing machine, and adhesive is sprayed on the cylindrical pit-shaped microstructures in even rows on the front cutting surface A1 and the back cutting surface A3 of each tooth, and the broach is left to stand for 4 minutes.
[0074] Step 7: Fig.13 As shown, the broach after the treatment in step six is placed in an electrostatic flocking machine, and nylon fibers are implanted in the cylindrical pit-shaped microstructures of even rows on the front cutting surface A1 and the back cutting surface A3 of each tooth. Fig.14 shown.
[0075] Step 8: Use a high-speed microscope to photograph the cylindrical pit-shaped microstructures of even-numbered rows on the front cutting surface A1 and the back cutting surface A3 of each tooth, and transmit the photographed images to a computer for analysis to determine whether the density of nylon fibers in the cylindrical pit-shaped microstructures of even-numbered rows on the front cutting surface A1 and the back cutting surface A3 of the tooth reaches a preset value (e.g., 2.5*10 4 Pieces / mm 2 ), if the density of the nylon fibers in any of the cylindrical pit-shaped microstructures does not reach a preset value, the nylon fibers in the corresponding cylindrical pit-shaped microstructures are removed, the broach is put back into the electrostatic flocking machine, and the nylon fibers are re-implanted into these cylindrical pit-shaped microstructures where the density of the nylon fibers does not reach a preset value.
[0076] Step nine: drying the broach after the processing in step eight to solidify the adhesive in the cylindrical pit-shaped microstructures in even rows on the front cutting surface A1 and the back cutting surface A3 of each tooth.
[0077] Step 10: Blow air on the broach processed in step 9 to remove the nylon fibers scattered outside the cylindrical pit-shaped microstructures on which the nylon fibers have been implanted.
[0078] Step 11: Fig.12 As shown, the broach is placed on the processing table of a precision glue dispensing machine, and adhesive is sprayed on each cylindrical pit-shaped microstructure on the two tooth sides A4 of each tooth, and the broach is left to stand for 4 minutes.
[0079] Step 12: Fig.13 As shown, the broach after the treatment in step 11 is placed in an electrostatic flocking machine, and lead and copper mixed fibers are implanted in each cylindrical pit-shaped microstructure on the two tooth sides A4 of each tooth. Fig.15 shown.
[0080] Step 13: Use a high-speed microscope to photograph each cylindrical pit-shaped microstructure on the two tooth sides A4 of each tooth, and transmit the photographed image to a computer for analysis to determine whether the density of the lead and copper mixed fiber in each cylindrical pit-shaped microstructure on the two tooth sides A4 of each tooth reaches a preset value (e.g., 2.5*10 4 Pieces / mm 2 ), if the density of the lead and copper mixed fiber in any cylindrical pit-shaped microstructure does not reach the preset value, the lead and copper mixed fiber in the corresponding cylindrical pit-shaped microstructure is removed, the broach is put back into the electrostatic flocking machine, and the lead and copper mixed fiber is re-implanted into these cylindrical pit-shaped microstructures where the density of the lead and copper mixed fiber does not reach the preset value.
[0081] Step 14: Dry the broach after the processing in step 13 to solidify the adhesive in each cylindrical pit-shaped microstructure on the two tooth side surfaces A4 of each tooth.
[0082] As a preferred embodiment, the adhesive is thermally conductive silicone grease.
[0083] More preferably, the dosage of the adhesive used in a single cylindrical pit-shaped microstructure is 0.001 ml.
Claims
1. A composite microstructure broach imitating crab claw hair, characterized by: The rake face of each tooth is provided with X1 rows and Y1 columns of cylindrical pit-shaped microstructures arranged in a rectangular shape, and the two opposite sides of the rectangle are parallel to the flank face and the side face of the tooth respectively; the flank face of each tooth is provided with X2 rows and Y2 columns of cylindrical pit-shaped microstructures arranged in a rectangular shape, and the two opposite sides of the rectangle are parallel to the rake face and the side face of the tooth respectively; the side faces of the teeth on both sides of each tooth are provided with X3 rows and Y3 columns of cylindrical pit-shaped microstructures arranged in a parallelogram shape, and the two opposite sides of the parallelogram are parallel to the rake face and the flank face of the tool respectively; the diameter D of the cylindrical pit-shaped microstructure is in the range of 0.2 to 0.3 mm, and the depth H is in the range of 1 to 2 mm. The diameter d of the carbon fiber, nylon fiber and lead and copper mixed fiber is in the range of 5 to 10 μm, and the length L of the carbon fiber, nylon fiber and lead and copper mixed fiber is in the range of 0.35 to 0.4 mm; the density of the carbon fiber, nylon fiber or lead and copper mixed fiber in the cylindrical pit-shaped microstructure is not less than 2.5*10 4 Pieces / mm 2 .
2. The composite microstructure broach imitating crab claw hair according to claim 1, characterized in that: The center distance L1 of two adjacent cylindrical pit-shaped microstructures in the same row on the front cutting surface, the rear cutting surface and the side surface of the tooth is within the range of 0.3-0.35mm, and the center distance L2 of two adjacent cylindrical pit-shaped microstructures in the same column is within the range of 0.3-0.35mm.
3. The composite microstructure broach imitating crab claw hair according to claim 2, characterized in that: The distance l between the center of the two rows of cylindrical pit-shaped microstructures on the front blade surface closest to the side surfaces of the two teeth and the adjacent side surfaces of the teeth min1 The distance from the center of the row of cylindrical pit-shaped microstructures closest to the blade to the back surface is l min2 The distance l from the center of the two rows of cylindrical pit-shaped microstructures on the side of the blade closest to the two sides to the adjacent side of the blade is min3 The distance from the center of the row of cylindrical pit-shaped microstructures closest to the blade to the front blade surface is l min4 are all 0.5 mm; the distance l from the center of a row of cylindrical pit-shaped microstructures closest to the rake face on the side of the tooth to the rake face min5 The distance from the center of the row of cylindrical pit-shaped microstructures closest to the back face to the back face is l min6 Both are 0.2mm.
4. The composite microstructure broach imitating crab claw hair according to claim 1, characterized in that: X1=4, Y1=30; X2=7, Y2=30; X3=10, Y3=8.
5. The composite microstructure broach imitating crab claw hair according to claim 1, characterized in that: The lead and copper mixed fiber comprises 40% of lead fiber and 60% of copper fiber.
6. A method for preparing a composite microstructure broach imitating crab claw hair according to any one of claims 1 to 5, characterized in that: The details are as follows: S1. Preheat the broach to be processed at 300°C for 30 minutes and air cool it to room temperature; S2, fixing the broach processed in step S1 on the workbench of a laser marking machine, inputting the parameters of the cylindrical pit-shaped microstructure into the laser marking machine; processing X2 rows and Y2 columns of cylindrical pit-shaped microstructures in rectangular distribution on the back face of each tooth of the broach, and processing X3 rows and Y3 columns of cylindrical pit-shaped microstructures in parallelogram distribution on the side face of each tooth; S3, placing the broach processed in step S2 into an ultrasonic cleaning machine for ultrasonic cleaning to remove debris, the cleaning time is greater than 1 minute, and drying is performed after cleaning; S4, fixing the broach processed in step S3 on the processing table of the tool tip microstructure single-point diamond tool vibration stamping device, inputting the parameters of the cylindrical pit-shaped microstructure into the tool tip microstructure single-point diamond tool vibration stamping device, and using the tool tip microstructure single-point diamond tool vibration stamping device to prepare a rectangularly distributed X1 row and Y1 column cylindrical pit-shaped microstructure on the rake face of each tooth of the broach; S5, placing the broach processed in step S4 into an ultrasonic cleaning machine for ultrasonic cleaning to remove debris, the cleaning time is greater than 1 minute, and drying is performed after cleaning; S6. Carbon fibers are implanted in the cylindrical pit-shaped microstructures in the odd-numbered rows on the front and rear blade surfaces, nylon fibers are implanted in the cylindrical pit-shaped microstructures in the even-numbered rows, and lead and copper mixed fibers are implanted in the cylindrical pit-shaped microstructures on the side surfaces of the blade teeth.
7. The method for preparing a composite microstructure broach imitating crab claw hair according to claim 6, characterized in that: The process for implanting carbon fiber, nylon fiber, and lead and copper mixed fiber is as follows: Step 1: Place the broach on the processing table of the precision glue dispensing machine, spray adhesive on the odd-numbered rows of cylindrical pit-shaped microstructures on the front and rear cutting surfaces of each tooth, and let it stand for 4 minutes; Step 2: Place the broach processed in step 1 into an electrostatic flocking machine, and implant carbon fibers into the cylindrical pit-shaped microstructures in odd rows on the rake face and the flank face of the blade teeth; Step 3, photographing the cylindrical pit-shaped microstructures in odd rows on the front blade face and the back blade face of each tooth with a high-speed microscope, and transmitting the photographed images to a computer for analysis to determine whether the density of the carbon fiber in the cylindrical pit-shaped microstructures in odd rows on the front blade face and the back blade face of each tooth reaches a preset value. If the density of the carbon fiber in the cylindrical pit-shaped microstructures does not reach the preset value, the carbon fiber in the corresponding cylindrical pit-shaped microstructures is removed, the broach is put back into the electrostatic flocking machine, and the carbon fiber is re-implanted in these cylindrical pit-shaped microstructures where the carbon fiber density does not reach the preset value; Step 4, drying the broach after the treatment in step 3 to solidify the adhesive in the odd-numbered rows of cylindrical pit-shaped microstructures on the rake face and the flank face of each tooth; Step 5, blowing air on the broach processed in step 4 to remove the carbon fibers scattered outside the cylindrical pit-shaped microstructures on the broach where the carbon fibers have been implanted; Step 6: Place the broach on the processing table of the precision dispensing machine, spray adhesive on the cylindrical pit-shaped microstructures in even rows on the rake face and the flank face of each tooth, and let it stand for 4 minutes; Step 7, placing the broach processed in step 6 into an electrostatic flocking machine, and implanting nylon fibers into the cylindrical pit-shaped microstructures in even rows on the rake face and the flank face of each blade tooth; Step 8, photographing the cylindrical pit-shaped microstructures of each even-numbered row on the front blade face and the back blade face of each tooth with a high-speed microscope, and transmitting the photographed images to a computer for analysis to determine whether the density of the nylon fiber in the cylindrical pit-shaped microstructures of each even-numbered row on the front blade face and the back blade face of the tooth reaches a preset value. If the density of the nylon fiber in the cylindrical pit-shaped microstructure does not reach the preset value, the nylon fiber in the corresponding cylindrical pit-shaped microstructure is removed, the broach is put back into the electrostatic flocking machine, and the nylon fiber is re-implanted in these cylindrical pit-shaped microstructures whose nylon fiber density does not reach the preset value. Step nine, drying the broach after the processing in step eight, so that the adhesive in the cylindrical pit-shaped microstructures in even rows on the rake face and the flank face of each tooth is solidified; Step 10, blowing air on the broach processed in step 9 to remove the nylon fibers scattered outside the cylindrical pit-shaped microstructures on the broach where the nylon fibers have been implanted; Step 11: Place the broach on the processing table of the precision glue dispensing machine, spray adhesive on each cylindrical pit-shaped microstructure on the two tooth sides of each tooth, and let it stand for 4 minutes; Step 12, placing the broach processed in step 11 into an electrostatic flocking machine, and implanting lead and copper mixed fibers into each cylindrical pit-shaped microstructure on the two tooth sides of each tooth; Step 13, photographing each cylindrical pit-shaped microstructure on the two tooth sides of each tooth with a high-speed microscope, and transmitting the photographed image to a computer for analysis to determine whether the density of the lead and copper mixed fiber in each cylindrical pit-shaped microstructure on the two tooth sides of each tooth reaches a preset value. If the density of the lead and copper mixed fiber in the cylindrical pit-shaped microstructure does not reach the preset value, then removing the lead and copper mixed fiber in the corresponding cylindrical pit-shaped microstructure, putting the broach back into the electrostatic flocking machine, and re-implanting the lead and copper mixed fiber in these cylindrical pit-shaped microstructures where the density of the lead and copper mixed fiber does not reach the preset value; Step 14: drying the broach after the processing in step 13 to solidify the adhesive in each cylindrical pit-shaped microstructure on the two tooth sides of each tooth.
8. The method for preparing a composite microstructure broach imitating crab claw hair according to claim 7, characterized in that: The adhesive is thermally conductive silicone grease.
9. The method for preparing a composite microstructure broach imitating crab claw hair according to claim 7, characterized in that: The amount of adhesive used in a single cylindrical pit-shaped microstructure was 0.001 ml.
Citation Information
Patent Citations
Micro-textured ZrVSiN Adaptive Coated Cutting Tools and Their Preparation Processes
CN106498393B
AlNbC / AlNbCN multilayer composite coated cutting tools and their preparation process
CN107177829B
A microtextured gradient coated cutting tool and its preparation method
CN110016642B
Cobweb-like microstructure broach with gradient wetted surface and preparation method thereof
CN111230213A
Crevice corrosion preparation method and device for composite microstructure on high-hardness surface
CN113512726A